Nonlocal Operators Are Chaotic - Lizama-Yanez, C (American Institute of Physics, 2020)
We characterize for the first time the chaotic behavior of nonlocal operators that come from a broad class of time-stepping schemes of approximation for fractional differential operators. For that purpose, we use criteria for chaos of Toeplitz operators in Lebesgue spaces of sequences. Surprisingly, this characterization is proved to be - in some cases - dependent of the fractional order of the operator and the step size of the scheme. © 2020 Author(s).